Integrating Everything The Integrated Practitioner - Amery, Justin (Taylor & Francis, 2014)
Health practice has always been many things, with many constraints and pressures. These things have changed over time and still vary from place to place. Being a practitioner here and now is, from one perspective, no different to the way it has always been. It involves integration. It involves weaving together many threads into one whole tapestry. It involves taking a constrained and limited palate and painting freely. It may be a science, it may be technical, it may be psychological, it may be spiritual, but it is always an art, because it integrates everything in order to create. And what we create is better health.' Justin Amery This extraordinary new series fills a void in practitioner development and well-being. The books take a reflective step back from the tick-box, target-driven and increasingly regulated world of 21st century health practice; and invite us to revisit what health and health practice actually are. Building carefully on the science and philosophy of health, each book addresses the messy, complex and often chaotic world of real-life health practice and offers an ancient but now almost revolutionary understanding for students and experienced practitioners alike: that health practice is a fundamentally creative and compassionate activity. The series as a whole helps practitioners to redefine and recreate their daily practice in ways that are healthier for both patients and practitioners. The books provide a welcome antidote to demoralisation and burn-out amongst practitioners, reversing cynicism and reviving our feeling of pride in, and our understanding of, health practice. By observing practice life through different lenses, they encourage the development of efficiency, effectiveness and, above all, satisfaction. The fourth book in the series, The Integrated Practitioner: Integrating Everything, considers the 'we', the 'me' and the 'other' perspectives of books 1-3 and integrates everything into 'health practice' as a single entity. It recognises the multifaceted nature of healthcare, its different constraints and varied pressures, but also views it from a new perspective, fostering a happier, healthier and more skilful whole within the real-life, complex and often messy world of health practice. Brilliantly written, practitioners, students and trainees and GP trainers will find the enlightening, witty, conversational style a joy to read.